Antihypertensive medications and risk of death and hospitalizations in US hemodialysis patients: Evidence from a cohort study to inform hypertension treatment practices. Issue 5 (February 2017) - Shafi, Tariq; Sozio, Stephen M.; Luly, Jason; Bandeen-Roche, Karen J.; St. Peter, Wendy L.; Ephraim, Patti L.; McDermott, Aidan; Herzog, Charles A.; Crews, Deidra C.; Scialla, Julia J.; Tangri, Navdeep; Miskulin, Dana C.; et al.
Abstract : Abstract: Antihypertensive medications are commonly prescribed to hemodialysis patients but the optimal regimens to prevent morbidity and mortality are unknown. The goal of our study was to compare the association of routinely prescribed antihypertensive regimens with outcomes in US hemodialysis patients. We used 2 datasets for our analysis. Our primary cohort (US Renal Data System [USRDS]) included adult patients initiating in-center hemodialysis from July 1, 2006 to June 30, 2008 (n = 33, 005) with follow-up through December 31, 2009. Our secondary cohort included adult patients from Dialysis Clinic, Inc. (DCI), a national not-for-profit dialysis provider, initiating in-center hemodialysis from January 1, 2003 to June 30, 2008 (n = 11, 291) with follow-up through December 31, 2008. We linked the USRDS cohort with Medicare part D prescriptions-fill data and the DCI cohort with USRDS data. Unique aspect of USRDS cohort was pharmacy prescription-fill data and for DCI cohort was detailed clinical data, including blood pressure, weight, and ultrafiltration. We classified prescribed antihypertensives into the following mutually exclusive regimens: β-blockers, renin–angiotensin system blocking drugs-containing regimens without a β-blocker (RAS), β-blocker + RAS, and others. We used marginal structural models accounting for time-updated comorbidities to quantify each regimen's association with mortality (both cohorts) and cardiovascular hospitalization (DCI-Medicare Subcohort). In the USRDS and DCI cohorts there were 9655 (29%) and 3200 (28%) deaths, respectively. In both cohorts, RAS compared to β-blockers regimens were associated with lower risk of death; (hazard ratio [HR]) (95% confidence interval [CI]) for all-cause mortality, (0.90 [0.82–0.97] in USRDS and 0.87 [0.76–0.98] in DCI) and cardiovascular mortality (0.84 [0.75–0.95] in USRDS and 0.88 [0.71–1.07] in DCI). There was no association between antihypertensive regimens and the risk of cardiovascular hospitalizations. In hemodialysis patients undergoing routine care, renin–angiotensin system blocking drugs-containing regimens were associated with a lower risk of death compared with β-blockers-containing regimens but there was no association with cardiovascular hospitalizations. Pragmatic clinical trials are needed to specifically examine the effectiveness of these commonly used antihypertensive regimens in dialysis patients. Abstract : Supplemental Digital Content is available in the text